An Improved Synthesis of the Antimicrobial Thymol- and Carvacrol-β-D-Glucopyranosides - Walker, Melanie; Robison, Ashlee; R. Collins, William (Letters in Organic Chemistry, 2016)
Thymol (1) and Carvacrol (2) are monoterpenoid natural products that display in vitro antimicrobial activity against Campylobacter jejuni and coli, food-borne pathogens found in animal distal guts/avian crops that commonly contaminate meat and poultry during processing. Recently, it has been shown that thymol-β-D-glucopyranoside (3), a glucosylated variant of the free monoterpenoid, also induces Campylobacter reductions within collected gut contents. Unfortunately, commercial sources of 3 are prohibitively expensive for large-scale use, and syntheses of glucosylated variants of either thymol or carvacrol are low yielding. Herein we report on an improved synthesis of both 3 as well as carvacrol-β- D-glucopyranoside (4). This synthesis utilizes phase transfer catalysis glycosylation conditions in lieu of the previously reported, low-yielding and expensive Koenigs-Knorr reactions.
Keywords: phase-transfer reactions